Epidemiology of Sports-Related Traumatic Hip Dislocations Reported in United States Emergency Departments, 2010-2019. Issue 5 (5th May 2022) - Moran, Jay; Cheng, Ryan; Schneble, Christopher A.; Mathew, Joshua I.; Kahan, Joseph B.; Li, Don; Gardner, Elizabeth C.
Background: Traumatic hip dislocations are rare injuries that most commonly occur in motor vehicle accidents. There is a paucity of literature that describes sports-related hip dislocations. Purpose: To estimate the incidence of sports-related hip dislocations and determine any sport- or sex-related epidemiological trends using the National Electronic Injury Surveillance System (NEISS) database. Study Design: Descriptive epidemiology study. Methods: Data regarding sports-related hip dislocations from 2010 to 2019 were retrieved from the NEISS, a database that catalogs injury information during emergency department visits from 100 hospitals across the United States to produce nationwide estimates of the injury burden. The estimated number of injuries was calculated using weights assigned by the NEISS database. The injuries were then stratified by sport and sex to determine any epidemiological patterns. Results: A total of 102 hip dislocation injuries were identified over the surveyed 10 years, indicating 2941 estimated injuries nationwide. Overall, 10 (9.8%) of 102 sports-related hip dislocations presented with concomitant acetabular fractures, representing an estimated 288 injuries nationally over 10 years. Male athletes sustained more sports-related hip dislocations than female athletes, with a relative incidence of 12.51 ( P < .001). Adolescents aged 15 to 19 years recorded the highest number of hip dislocations. There were 17 sports identified as having caused at least 1 hip dislocation over the 10-year period. More hip dislocation injuries were sustained from contact sports (91.2%) than noncontact sports (8.8%) ( P < .001). Football (estimated 164 injuries per year; 55.6%), snowboarding (28 per year; 9.5%), skiing (26 per year; 8.8%), and basketball (21 per year; 7.1%) had the highest rates of hip dislocation. Additionally, 43 (82.7%) football-related injuries were caused by tackling mechanisms, and 9 (17.3%) were caused by nontackling mechanisms ( P < .001). Conclusion: The incidence of traumatic sports-related hip dislocations was extremely low in the United States during the study period. Male adolescents, aged 15 to 19 years, sustained the greatest number of injuries during football. Significantly more hip dislocations occurred in contact sports, most commonly football, snowboarding, skiing, and basketball, compared with noncontact sports. As adolescent athletes may have limited treatment options if osteonecrosis occurs, these data serve to increase the clinical awareness of these injuries.